(untitled) (Bulletin KNOB, 2023)
In the post-war historiography of Dutch modern architecture, the monograph of Gerrit Rietveld written by the American architectural historian Theodore Morey Brown (1958) played a pioneering role. The Work of G. Rietveld, Architect was the first monograph of a by then already internationally renowned Dutch architect and since it was written in English it was also the only source of detailed information about Rietveld for an international readership. Brown was the first art historian in the Netherlands to write a dissertation on a living architect; as such, his book signalled the start of modern architectural history as practised by art historians. Yet despite the fact that it is almost impossible to overstate the significance of Brown’s study, the book remains until this day a curiosity. Why was the first scholarly work on Rietveld written by an American scholar and published in the English language? Who was Theodore Morey Brown and how did he end up at a Dutch university in the 1950s? This article examines the history of Brown’s book: its genesis from a research initiative by post-war Dutch professors of art history to the contents of the final book. It also discusses the international historiographical debate in which Brown participated. Brown’s book heralded a new era in the relationship between the art historian and the architect, one that was connected with the challenge to write contemporary history from an ideologically engaged attitude. As an ‘operative history’ Brown’s book was distinguished by its collaborative nature. While it was a book about a single architect written by a single historian, in the background there was a ‘team Rietveld’ consisting of, among others, the historian Pieter Singelenberg and the designer Truus Schröder-Schräder, who were vital to its creation. Only with the help of these people could the work of Rietveld be made accessible to a foreign scholar who, upon arrival in the Netherlands, did not speak the Dutch language. This article argues that Brown’s book was important not only for the historiography on Rietveld. The book also had an institutional significance as it ushered in the study of modern architectural history by art historians in the Netherlands.